Effect of Brewing Time on the Psychochemical and Antioxidant Activity of Green Tea Bag - Ayuningtyas, Ukhti; Rufaida, Zahrah; Septiani, Widya Prasetyawati; Shabri,; Harianto, Sugeng; Maulana, Hilman; Prawira-Atmaja, M. Iqbal (JURNAL AGROINDUSTRI HALAL, 2023)
Teabags are commonly used because of their practical use and benefits as antioxidants. However, there are still few studies that report the effect of brewing time of tea bags on their bioactive compounds. This study aims to determine green tea bags' psychochemical properties and antioxidant activity with different brewing times (1, 3, 5, 7, 9, 12, and 15 minutes). The results showed that the length of steeping time influenced the increase in total polyphenols, flavonoids, and antioxidant activity in green tea bags. The highest rehydration ratio value for product A was in the 3rd minute, which was 3.74 g/g, while in product B, it was 3.36 g/g at the 15th minute. In contrast, the highest swelling rate value occurred in the 15th minute with 372.79% and 236.31% in products A and B, respectively. Products A and B had the highest total flavonoids at 12 minutes of brewing time with 132.41 mg Q.E/g and 144.63 mg Q.E/g, respectively. Product A had the highest free radical inhibition activity at the 7th minute, while product B at the 9th-minute steeping was 56.54% and 73.73%, respectively. Pearson Correlation shows a positive correlation between total polyphenols, flavonoids, and antioxidant activity in green tea bags. The results of this study are expected to be a reference and education of reasonable green tea brewing procedures for consumption by the public.